RESISTÊNCIA DE COLMO À PENETRAÇÃO COMO PREDITOR DA QUALIDADE DE COLMOS EM MILHO - Oliveira, Rodrigo Martins de (2015)
Annual losses of up to 25% of world corn production are stimated as a result of stalk lodging and root lodging. The use of resistant hybrids is the main method of control, though only use the visual evaluation is very limited. In this context, it is crucial to find methods to evaluate the quality of stalks with high correlationship with stalk loding that could be effective to detect level differences of resistance to stalk lodging. The objective of this study was to estimate the correlationship between agronomic characteristics and attributes associated with stalk lodging of corn hybrids and their inbred lines. Additionally, select genotypes that simultaneously have the highest number of characteristics associated with stalk quality and grain yield by principal component analysis. There were performed four experiments using corn hybrids and one experiment with inbred lines for evaluation of corn stalk penetration resistance as predictor of corn stalk quality in the 2013/2014 season. The experimental design was a randomized block design with twelve treatments and four reps for experiments with hybrid and sixteen treatments and three reps for the experiment with inbred lines. The results of the hybrids and inbred lines experiments were submited to Pearson correlation analysis through the GENES statistical software, and principal component analysis was performad by the R sorftware 2.15.2. The physical stalk quality represented mainly by stalk lodging, root lodging and corn stalk penetration resistance proved to be limiting for the selection of superior corn genotypes,because corn stalk lodging affected negatively the grain yield in corn hybrids. The stalk penetration resistance evaluation in inbred lines showed a significant negative correlation of 60% with stalk lodging, which makes this evaluation suitable for use to select inbred lines with enhanced physical quality of the stalks, enabling the detection of differences in stalk lodging resistance levels from the inbred lines. Using the principal component analysis was possible the identification of the corn inbred lines L2, L3, L6, L13 and L14, also the hybrids P30F53YH,30A37PW, DKB240PRO2 and H14 with the most favorable characteristics for stalk physical quality for corn grain yield.